Evaluation of pain perception using a vibrating toothbrush during the administration of local anesthesia in children: A randomized clinical trial - Meerza Alam Pinjari; SVSG Nirmala; Sivakumar Nuvvula (Contemporary Pediatric Dentistry)
Aim: Effective pain management is a critical and challenging aspect of behavior management in children during dental procedures. Among nonpharmacological methods for achieving painless local anesthesia (LA), devices utilizing the vibrotactile method have shown promise. This study aimed to evaluate the effectiveness of a vibrating toothbrush in alleviating pain during the administration of an Inferior Alveolar Nerve Block (IANB) in children aged 6–11 years. Methods: A randomized clinical trial was conducted involving children aged 6–11 years requiring mandibular local anesthesia. Fifty-two participants were randomly assigned to two groups: Group 1 received topical anesthetic spray, and Group 2 used a vibrating toothbrush. Pain during injection was objectively assessed using the Sound Eye Motor (SEM) scale, while subjective pain after LA administration was evaluated using the Faces Pain Scale-Revised (FPS-R). Pain scores were compared between groups using the Mann-Whitney U test. Results: The mean FPS-R score for the topical anesthetic spray group was 4.26, compared to 2.53 for the vibrating toothbrush group, demonstrating a statistically significant difference (P = 0.03). The mean SEM score for the vibrating toothbrush group was lower (2.06) than that of the topical anesthetic spray group (1.66), though the difference was not statistically significant (P = 0.17). Conclusions: The vibrating toothbrush proved more effective in reducing pain compared to topical anesthetic spray during the administration of mandibular anesthesia in children.